2019
DOI: 10.1016/j.ijms.2019.116177
|View full text |Cite
|
Sign up to set email alerts
|

Dueling electrospray implemented on a traveling-wave ion mobility/time-of-flight mass spectrometer: Towards a gas-phase workbench for structural biology

Abstract: Highlights• Covalent chemistry was performed in an ion mobility/mass spectrometer (IM/MS).• The effects of various parameters on the extent of reactions was observed.• Angiotensin I and ubiquitin were covalently labeled in the gas-phase.• Ion/ion reactions modify ions with solution-like conformations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 54 publications
2
29
0
Order By: Relevance
“…1 C), proton transfer becomes favorable as the transition state is more disordered than the transition state for covalent bond formation, evidenced by a positive activation entropy for proton transfer versus a negative activation entropy for covalent bond formation. This reflects the ability in previous experiments to tune the reaction conditions in the trap traveling wave cell appropriately 12,32 such that covalent bond formation was the only observed ion/ion product, ensuring that intramolecular proton transfer to sulfo-benzoyl HOAt does not measurably occur, in agreement with the measurements here that covalent bond formation is the kinetically favored product.…”
Section: Covalent and Proton Transfer Reactionssupporting
confidence: 86%
“…1 C), proton transfer becomes favorable as the transition state is more disordered than the transition state for covalent bond formation, evidenced by a positive activation entropy for proton transfer versus a negative activation entropy for covalent bond formation. This reflects the ability in previous experiments to tune the reaction conditions in the trap traveling wave cell appropriately 12,32 such that covalent bond formation was the only observed ion/ion product, ensuring that intramolecular proton transfer to sulfo-benzoyl HOAt does not measurably occur, in agreement with the measurements here that covalent bond formation is the kinetically favored product.…”
Section: Covalent and Proton Transfer Reactionssupporting
confidence: 86%
“…cell (e-MSion, Corvallis, OR). Instrumental details for the ion/ion reactions 24,37 and ExD cell 33 have been described previously. The NanoLockspray source was used with proteins infused through the sample sprayer and anionic reagents through the reference sprayer..…”
Section: Methodsmentioning
confidence: 99%
“…22 Gas-phase ion/ion reactions have also been used to report on threedimensional structure of protein cations formed from native-like or denaturing solutions. [23][24][25] A combination of experimental 4,7,[26][27][28][29] and computational studies [30][31] have shown that under carefully-controlled experimental conditions, the solution structures of electrosprayed peptides and proteins is conserved upon electrospray ionization, making methods for probing gas-phase three-dimensional structures of proteins an extremely valuable addition to structural biology techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All the experiments were performed on a Synapt G2-Si High Definition Mass Spectrometer (Waters Corporation, Wilmslow, U.K.), equipped with electron transfer dissociation (ETD), a NanoLockspray source, an external electrospray voltage control module (GAA Custom Electronics LLC, Kennewick, WA), and an ExD cell (e-MSion, Corvallis, OR). Instrumental details for the ion/ion reactions 24,37 and ExD cell 33 have been described previously. The NanoLockspray source was used with proteins infused through the sample sprayer and anionic reagents through the reference sprayer..…”
Section: Methodsmentioning
confidence: 99%